Entrance to Aurora College, Yellowknife/North Slave Campus ... - Campbell, Sandy (University of Alberta Library, 2015)
Aurora College Yellowknife/North Slave Campus is located at 50 Ave. and 54 St. in Northern United Place. This is one of three campuses of this college, the others being in Inuvik and Fort Smith. Two of the heavily subscribed programs offered here are Nursing and Social Work. This campus currently has about 250 students. There is a library at this site. ...